2010
DOI: 10.3844/jssp.2010.447.452
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Background Factors and Female Marital Satisfaction

Abstract: Problem statement: In spite of the importance of marital satisfaction in couple relation, there is a little research in the Iranian context that examined the relationship between background factors and marital satisfaction. Thus, this study examined the relationship between duration of marriage, number of children, years of education and family income with female marital satisfaction. Approach: The study was carried out among a sample of 337 wives in Shiraz City, Iran. The Kansas Marital Satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A 2014 study by Zanjani and Baghiat showed that there were significant statistical differences between existence of children and marital satisfaction (9). In some of the studies, relationship between number of children and marital satisfaction has been inversely statistically significant (10, 20, 28, 37), While in the 2014 study by Mirghaforvand and colleagues and Zanjani and Baghiat, these differences were not statistically significant (9, 38). …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A 2014 study by Zanjani and Baghiat showed that there were significant statistical differences between existence of children and marital satisfaction (9). In some of the studies, relationship between number of children and marital satisfaction has been inversely statistically significant (10, 20, 28, 37), While in the 2014 study by Mirghaforvand and colleagues and Zanjani and Baghiat, these differences were not statistically significant (9, 38). …”
Section: Resultsmentioning
confidence: 98%
“…Many studies in Iran have shown positive significant statistical relationship between educational level and marital satisfaction (10, 23–28). However, it does not mean lack of this will result in incompatibility and lack of understanding between couples, because such factors are interpreted based on the intellectual and epistemic background of the woman and the man (13, 22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyadic adjustment has been shown to be linked with both physiological and psychological well-being in couples (Kiecolt-Glaser & Newton, 2001;Robles et al, 2014;Waite & Gallagher, 2000). Beyond its contribution to well-being, dyadic adjustment is also a key variable for successful intimate relationships and can help to strengthen the quality of the relationship and prevent breaking up (Bui et al, 1996;Gottman, 1994;Karney & Bradbury, 1995;Mirfardi et al, 2010). Therefore, examining factors that contribute to relationship adjustment in couples can contribute to a better understanding of both individual and dyadic effects that affect partners' dyadic adjustment.…”
Section: Literature Reviewmentioning
confidence: 99%